Two‐Dimensional Maps of In Situ Ionospheric Plasma Flow Data Near Auroral Arcs Using Auroral Imagery. Issue 4 (12th April 2019) - Clayton, Robert; Lynch, Kristina; Zettergren, Matt; Burleigh, Meghan; Conde, Mark; Grubbs, Guy; Hampton, Don; Hysell, David; Lessard, Marc; Michell, Robert; Reimer, Ashton; Roberts, T. Maximillian; et al.
Abstract: Some existing auroral data products are insufficient for ionospheric simulation input on subkilometer spatial scales and high (second) time resolution near the boundaries of arc structures. Ideally, two‐dimensional data maps of the relevant parameters over these small scales would provide models with constraining inputs. Available in situ data have the time and spatial resolution for small‐scale features but only provide a 1‐D cut through the structure. Ground‐based data can provide 2‐D maps but have lower resolution in time and space than is required to accurately interpret the small‐scale structure near an arc. This paper provides a method to construct two‐dimensional maps of auroral parameters from the combination of one‐dimensional in situ data cuts with two‐dimensional ground‐based (and time dependent) camera imagery. Arc boundaries for each image are defined, and the available 1‐D ionospheric flow data are replicated into many 1‐D cuts at different points along the arc, yielding an irregularly sampled 2‐D flow map. These mapped data are fitted to a regular grid via a divergence minimization routine to generate a regularly sampled flow field that is enforced as divergence free. Comparison of the generated 2‐D data maps to available information from camera inversions and other data products is shown, as are assumptions made through the replication process and alternative strategies. Reconstructed flow maps are shown to maintain the small‐scale features near arc boundaries while increasing the dimensionality to 2‐D and to follow the time evolution of the arc structure by comparisons to imagery. The average electric field magnitudes per unit area of the reconstructed and divergence‐minimized flow fields are also calculated and compared between different data sources. Key Points: We provide a new procedure for mapping ionospheric flow data using ground camera imagery We evaluate mapped ionospheric plasma flow data in context of existing measurements We compare model outputs with existing measurements and auroral assumptions